Environmental Sustainability of Current Waste Management Practices (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Environmentally sustainable and economic waste management is of significant importance to various fields, including the healthcare, mining, industrial, metal-processing, municipal and commercial sectors. This book provides a global perspective and covers a wide range of state-of-the-art topics on waste management, recycling, material and energy recovery, industrial waste, etc. Information in the form of in-depth reviews and research articles will be a valuable resource for academics, professionals and regional as well as international organizations.